New sources of higher green matter quality for perennial grasses in the southern forest-steppe environments of West Siberia - O. A. Yusova (Труды по прикладной ботанике, генетике и селекции)
Background. Perennial grasses are essential in the development of field forage production in West Siberia. Very pronounced continental climate of the cropping areas in Siberia leads to increased demands on the cultivars. The objects of the study were cultivated varieties of perennial grasses (awnless bromegrass and variegated alfalfa). The aim of the work was to identify the sources of high-quality green matter in variegated alfalfa and awnless bromegrass. Materials and methods. The experimental part of the work was carried out over the period of 2011–2016 on the experimental fields of Omsk Agrarian Scientific Center, located in the southern forest steppe near Omsk. Agricultural practice was conventional for West Siberia. Analysis of variance was used in mathematical data processing; stability and plasticity parameters were calculated. Results. The content of protein and cellulose fiber in the green biomass of perennial grasses was mainly influenced by the weather conditions of the year: 84.1 and 76.5% in alfalfa, 93.9 and 91.2% in bromegrass, respectively. A reduction of cellulose fiber content in the studied crops contributed to an increase in raw protein content (r = –0.348 and –0.335) and in feed value units (r = 0.544 and 0.352 for alfalfa and bromegrass, respectively). Higher yields had a negative impact on feed value units (r = –0.402 and –0.713). Besides, the yield of awnless bromegrass demonstrated a significant negative correlation with protein content (r = –0.617) and a positive one with cellulose fiber (r = 0.744). The yield of variegated alfalfa showed a weak degree of interdependence with protein and cellulose fiber contents (r = 0.239 and 0.306).). Conclusion. High responsiveness to improved environmental conditions and high stability (bi > 1, σ2 d < 1) were observed in the alfalfa cultivars ‘Omsky 7’, ‘Elbrus’ (protein content); ‘Flora 5’ and ‘Flora 6’ (protein content, feed value units, and green matter yield), and the bromegrass cultivars ‘SibNIISKhoz 99’ (protein content, feed value units, and green matter yield) and ‘Titan’ (feed values units). During the period from 2011 through 2016, the best examples in yield and in a set of green matter quality characteristics were selected: the intensive-type alfalfa lines SP-2-99/91-267 and SP-2-99/01-282, extensive-type alfalfa line SP-2-99/01-132, and the line of bromegrass SP-2-06/08-28, which was intensive-type in protein content and feed value units, and extensive-type in cellulose fiber content and green matter yield.